The groundwater governance toolbox: Elements to increase sustainability of groundwater use in Africa - ElDidi, Hagar (2023)
Hagar ElDidi POLICY SEMINAR Groundwater: Potential and Pitfalls for Africa 2023 UN Water Conference Side Event MAR 20, 2023 - 8:00 TO 9:30AM EDT